Money in the life of townswomen before the Battle of White Mountain (Theatrum historiae, 2010)
This study focuses on the relationship women had with money in Bohemian towns before the Battle of White Mountain. The introduction takes account of the interest of historiography in researching women’s issues in early modern towns in general. In parti- cular it returns to the idea of the emancipation of Renaissance women in the older literature and the opinions of contemporary historiography as regards this topic. It subsequently recapitulates the role and form of money in the life of townswomen in their individual lifecycles. From the commemorative valuable coins that were placed in the cradle, through the coins used to adorn jewellery, to the cash girls received in the form of a dowry. Attention also briefly focuses on the education of town girls in large numbers. Then, taking the royal town of Louny as an example, it focuses attention on the individual types of sources which could show the relationship townswomen had with money. These are mostly sources of a financial nature, such as property censuses (valuations) of burgher assets, which identified a small group of Louny townswomen as the owners of extensive property. Records of trade and craft charges were also used, where women were mostly listed as greengrocers or distillers. What also proved to be of interest were the sources relating to inheritances, inventories and last wills. There is even a mention of lists of widows who levied money as so called “herwet”. In the light of the sources, the relationship towns- women had towards money was a multifaceted one. They appear as independent farmers, traders or merchants wherever the law or the situation permitted. Most, however, remained in the household, which was their principal domain for the whole of the early modern times. The study concludes by saying that if a townswoman had access to money – inherit- ed it, managed to earn it and count it, she could do what she liked with it – in a certain sense money opened up a public space for her. Not a space associated with local govern- ment or politics, but in the economic sphere or in social and cultural life, in the broad sense of the words.